Bioinspired Fluffy Fabric with In Situ Grown Carbon Nanotubes for Ultrasensitive Wearable Airflow Sensor. Issue 11 (3rd February 2020) - Wang, Haomin; Li, Shuo; Wang, Yiliang; Wang, Huimin; Shen, Xinyi; Zhang, Mingchao; Lu, Haojie; He, Maoshuai; Zhang, Yingying
Abstract: Recently, electronic skin and smart textiles have attracted considerable attention. Flexible sensors, as a kind of indispensable components of flexible electronics, have been extensively studied. However, wearable airflow sensors capable of monitoring the environment airflow in real time are rarely reported. Herein, by mimicking the spider's fluff, an ultrasensitive and flexible all‐textile airflow sensor based on fabric with in situ grown carbon nanotubes (CNTs) is developed. The fabric decorated with fluffy‐like CNTs possesses exceptionally large contact area, endowing the airflow sensor with superior properties including ultralow detection limit (≈0.05 m s −1 ), multiangle airflow differential response (0°–90°), and fast response time (≈1.3 s). Besides, the fluffy fabric airflow sensor can be combined with a pristine fabric airflow sensor to realize highly sensitive detection in a wide airflow range (0.05–7.0 m s −1 ). Its potential applications including transmitting information according to Morse code by blowing the sensors, monitoring increasing and decreasing airflow velocity, and alerting blind people walking outside about potential hazard induced by nearby fast‐moving objects are demonstrated. Furthermore, the airflow sensor can be directly integrated into clothing as stylish designs without sacrificing comfortness. It is believed that the ultrasensitive all‐textile airflow sensor holds great promise for applications in smart textiles and wearable electronics. Abstract : Inspired by the spider's fluffy hair, an ultrasensitive and flexible all‐textile airflow sensor is fabricated based on a fluffy fabric with in situ grown hair‐like carbon nanotubes on a silk fabric. The airflow sensor shows high sensitivity, ultralow detection limit, multi‐angle airflow detection capability, fast response, and wide detection range, promising wide potential applications in wearable electronics.